6=2(y+2)6=2(y+2)6=2(y+2)

Simple and best practice solution for 6=2(y+2)6=2(y+2)6=2(y+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6=2(y+2)6=2(y+2)6=2(y+2) equation:



6=2(y+2)6=2(y+2)6=2(y+2)
We move all terms to the left:
6-(2(y+2)6)=0
We calculate terms in parentheses: -(2(y+2)6), so:
2(y+2)6
We multiply parentheses
12y+24
Back to the equation:
-(12y+24)
We get rid of parentheses
-12y-24+6=0
We add all the numbers together, and all the variables
-12y-18=0
We move all terms containing y to the left, all other terms to the right
-12y=18
y=18/-12
y=-1+1/2

See similar equations:

| Y=6x^2+36x-5 | | -3x-125=115+7x | | 2x-3=4x2-5x+1 | | 2=v-86/6 | | 5(11/4-y/8)+2y=22 | | 3x+1=3x-5/2 | | g/3+16=18 | | q/8+75=82 | | 5(1-x)^2-6(^2-3x-7)=x(x-3)-2x(x+5)-2 | | 9/7=3/c | | 2(1+10^3x)=5 | | 2x/6+10=2/3-2x | | 24/r-20+24/r+10=30 | | X/3+5=x-9 | | 1/5=x/16 | | 7d+12-4d-3=0 | | (4n-20)=20+3n | | 12n-8=11n+4+n-8 | | Y=-x^2+6x+27 | | 14x-9=14+x+1 | | 2(1+10^(3x))=5 | | 4x-9=14+x+11 | | 8x+5=3x+2 | | v/3+13=15 | | x=x0 | | 4x-9=14+x+1 | | 2x=4/3x+20 | | -10x=-9x-19 | | 2w+2w+4/1/4=124/1/2 | | 4(1-5x)=-96 | | 2(x-18)=-44 | | 7b-21-7b=14b+6-7b |

Equations solver categories